ANALISIS SALURAN DAN MARGIN PEMASARAN IKAN BANDENG DI KECAMATAN SEDATI KABUPATEN SIDOARJO JAWA TIMUR - Prayoto, Prayoto; Nugraha, Jefri Putri; Waluyo, Buyung Purnomo; Hamdani, Hamdani; Priono, Bowo; Wartini, Sri (Chanos Chanos, 2022)
This study aims to determine the marketing channels of the milksfish, farmer’s share, and the marketing efficiency of the milksfish in Sedati District, Sidoarjo Regency. The design of this study was a descriptive method of sampling using proportionate stratified random sampling and  snowball sampling. Research has three types of marketing channel in sedati, district sidoarjo. The first line from the farmers' farm directly to the consumer  of the farmer’s share is 100 %, channel two from the farmers' farm chain to the traders, to the retailers, and then to consumer of  the farmer’s share is 71,4 %., and a third line from the farmers' farm to the big traders' , and to of  the farmer’s share is 82.8 %. The analysis shows that all three marketing channels are efficient because the cost part the farmer receives is over 50 %.